Clinical and etiological profile of new-onset seizures in adult patients: A cross-sectional study - Sivakumaran K; Jacinth Preethi J; Sinrasu P; Manikandan V (Asian Journal of Medical Sciences, 2023)
Background: In terms of the severity of the disease, the nature of the sickness, and its effects on the individual, the family, and the community, seizure disorder is a significant public health concern. Aims and Objectives: This study evaluated the clinical and etiological profile of new-onset focal or generalized seizures in adult patients. Materials and Methods: A cross-sectional study was conducted with 100 new-onset seizure patients admitted to the Government Ariyalur Medical College Hospital. A detailed history was taken from the relatives about the type of seizure and comorbid conditions. An examination of the central nervous system was done to find any underlying neurological deficits. Investigations done in all patients were blood sugar, urea, creatinine, serum electrolytes, and liver function tests. ECG, chest X-ray, electroencephalographic, and computerized tomography of the brain. Magnetic resonance imaging brain was done in the indicated cases. Results: Of the 100 patients, 76% were males and 24% were females. The majority of the patients belonged to the age group of 41–60 years (40%). The most common type of seizure observed was the generalized tonic-clonic type (49%), followed by the focal type of seizure (23%). Of the various comorbid illnesses observed, diabetes mellitus was seen in about 41% of the patients; hypertension was seen in 40% of the patients; chronic kidney disease was seen in 24%; and cerebrovascular diseases were seen in 15%. The commonest etiology of new-onset seizures observed in this study was metabolic causes, constituting 41% of the cases, cerebrovascular diseases (32%), and alcohol-related seizures (10%). Conclusion: Accurate identification of the cause of adult-onset seizures is crucial, and knowledge of clinical and etiological profiles will facilitate better treatment.